PRODUCTION OF FRAGRANCE ESTERS FROM FDSEL OIL BY MYCELIAL LIPASE OF RHIZOPUSARRHIZUS (Biological Sciences - PJSIR, 2022)
The properly dried and defatted mycelium of Rhizopus arrhizus constitutes a naturally immobilized lipase. Themycelium was used to synthesize flavouring esters from fusel oil by esterification in organic solvents. Differentparameters like reaction medium, temperature, substrate concentration .and moisture level were optimized for thesynthesis of butyrate esters offusel oil. The mycelium was repeatedly used in batch reactions and was found to have highefficiency and good operational stability. The halflife of the mycelial lipase was greatly int1uenced by the concentrationof substrates, i.e. the residual activity remained about the same after 20 cycles with low concentrations of substrates(0.1 Meach). However, when concentrations of butyric acid and fusel oil were high, the rhyceliumrapidly lost its activity.